Efecto de una intervención con ejercicio físico y orientación nutricional sobre componentes del síndrome metabólico en jóvenes con exceso de peso (2013)
ABSTRACT: Interventions with physical exercise and nutritional guidance show changes in overweight among young people suffering from the metabolic syndrome (MS); nevertheless, their characteristics and results vary. Objective: To assess the effect of an intervention with physical exercise and nutritional guidance on components of the MS among overweighted young people. Materials and methods: Longitudinal study with an assessment before and another after the intervention in nine young people aged 11 to 17 years. Anthropometric aspects, resting heart rate, peak oxygen consumption (VO2peak), insulinemia, HOMA, and components of the MS were assessed. Intervention consisted of 12 weeks of supervised exercise, three 90-minute sessions/week (aerobic and strength), plus two unsupervised sessions; the weekly supply of fruits and vegetables in order to cover the five recommended daily servings, and individual and group nutrition education. Results: With the intervention waist circumference decreased from 90.5 ± 11.0 to 88.1 ± 9.9 cm; BMI from 30.2 ± 5.8 to 29.3 ± 5.6 kg/m2 ; total body fat from 39.8 ± 13.0 to 34.3 ± 9.0%; glycemia from 86.0 ± 8.6 to 83.1 ± 5.0 mg/dL; insulinemia from 23.2 ± 9.8 to 19.4 ± 7.6 µU/mL; HOMA-IR from 2.89 ± 1.21 to 2.39 ± 0.93; resting heart rate from 87.9 ± 4.3 to 78.2 ± 5.5 rpm, and VO2peak increased from 36.3 ± 5.1 to 38.5 ± 4.1 mL/kg/min. Four out of six young people with the diagnosis of MS at the beginning of the study did not present it at the end. Conclusions: Participating in an exercise program and increase in the consumption of fruits and vegetables among overweighted young people with components of the MS produced positive modifications in body composition, VO2peak, resting heart rate, and glycemia, as well as in the components and prevalence of the MS.